Pengaruh Latihan Shuttle Run dan Lari Zig-Zag Terhadap Keterampilan Dribblingdalam Permainan Bola Basket pada Siswa SMP - Mawardinur Mawardinur; Susan Lumbangaol (INSPIRETECH GLOBAL INSIGHT & (ISORI KAMPAR), 2024)
The study aimed to examine the impact of shuttle run and zig-zag exercises on enhancing dribbling skills in junior high school basketball players. An experimental design utilizing a pretest-posttest control group was implemented. A sample of 60 students aged 13-15 was randomly assigned to three groups: shuttle run (n=20), zig-zag run (n=20), and control (n=20). The exercise regimen spanned 8 weeks, with sessions occurring three times weekly, each lasting 50 minutes. Dribbling proficiency was assessed using AAHPERD standard tests pre- and post-intervention. Statistical analysis was conducted via one-way ANOVA and Tukey's post-hoc test. Findings indicated both exercise modalities significantly enhanced dribbling skills compared to the control group (p < 0.05). Although zig-zag exercises yielded greater improvement (M = 3.8, SD = 1.2) than shuttle runs (M = 3.2, SD = 1.1), the difference was not statistically significant (p = 0.09). In summary, both shuttle run and zig-zag exercises were effective in advancing dribbling skills, with a pronounced improvement trend in zig-zag running.